2018
DOI: 10.3171/2017.4.jns152954
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled study comparing 2 surgical techniques for decompressive craniectomy: with watertight duraplasty and without watertight duraplasty

Abstract: Rapid-closure DC without watertight duraplasty is a safe procedure. It is not associated with a higher incidence of surgical complications (CSF leak, wound infection, brain abscess, or subgaleal fluid collections), and it decreased surgical time by 31 minutes on average. There was also a hospital cost reduction of $420.00 USD (23.4% reduction) per procedure. Clinical trial registration no.: NCT02594137 (clinicaltrials.gov).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 17 publications
4
27
0
2
Order By: Relevance
“…Regarding supratentorial craniotomies, our results are in line with other studies that the watertight dural closure is not necessarily associated with an increased rate of complications [7,42]. Even in the case of larger surgeries such as decompressive craniectomies, complications related to non-watertight dural closure seem to be negligible [21,50], and may be more related to quality and technique of skin closure. We did not observe differences in outcome caused by skin closure techniques using staples or stitches.…”
Section: Effect Of Other Surgical Variables On Outcome Parameterssupporting
confidence: 90%
“…Regarding supratentorial craniotomies, our results are in line with other studies that the watertight dural closure is not necessarily associated with an increased rate of complications [7,42]. Even in the case of larger surgeries such as decompressive craniectomies, complications related to non-watertight dural closure seem to be negligible [21,50], and may be more related to quality and technique of skin closure. We did not observe differences in outcome caused by skin closure techniques using staples or stitches.…”
Section: Effect Of Other Surgical Variables On Outcome Parameterssupporting
confidence: 90%
“…Likewise, clinical profile and injury mechanisms of the patients in the present study was consistent with previous studies, 19,23,24 thus confirming the need for more assertive traffic policies as a measure to prevent TBI. 25,26 Vieira and colleagues 27 also conducted a study in HR and found that DC without watertight duroplasty is not associated with a higher incidence of post-operative complications, frequency of CSF leakage, or infections. Moreover, DC patients had decreased surgical time by 31 min on average, resulting in a reduction in hospital costs for treatment of critically ill patients, especially those with severe TBI, since they configure greater demand.…”
Section: Discussionmentioning
confidence: 99%
“…It appears intuitive that a meticulous augmentative duraplasty and watertight scalp closure would prevent the exodus of CSF from the wound and reduce infection risk. However, a recent randomized controlled trial where watertight duraplasty was compared with rapid-closure DC without watertight duraplasty, there was no statistically significant difference in complications like CSF leak between the two groups of 29 patients each ( 30 ). Rapid closure DC without water tight duraplasty was on an average 31 min faster and hence cheaper.…”
Section: Early Complicationsmentioning
confidence: 99%